2021
DOI: 10.3390/nu13103466
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Cocoa Flavanols Enhance Mitochondrial Function in Skeletal Muscle and Modify Whole-Body Metabolism in Healthy Mice

Abstract: Mitochondrial dysfunction is widely reported in various diseases and contributes to their pathogenesis. We assessed the effect of cocoa flavanols supplementation on mitochondrial function and whole metabolism, and we explored whether the mitochondrial deacetylase sirtuin-3 (Sirt3) is involved or not. We explored the effects of 15 days of CF supplementation in wild type and Sirt3-/- mice. Whole-body metabolism was assessed by indirect calorimetry, and an oral glucose tolerance test was performed to assess gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 73 publications
(106 reference statements)
0
5
0
Order By: Relevance
“…Oral administration of NAD + precursors, such as tryptophan, nicotinic acid (niacin), nicotinamide, and nicotinamide riboside (NR), could increase tissue NAD + levels 525 , 526 . Food supplement cocoa flavanol is shown to boost the NAD + and NADH content, stimulate sirtuin metabolism, reduce cellular H 2 O 2 production as well as OxS, and improve mitochondrial function in PASC patients 527 . Increasing NAD + levels could also stabilize telomeres and help recovery of elderly PASC patients 528 .…”
Section: Long-covid/pasc: Precision Nutrition To Reset Virus-induced ...mentioning
confidence: 99%
“…Oral administration of NAD + precursors, such as tryptophan, nicotinic acid (niacin), nicotinamide, and nicotinamide riboside (NR), could increase tissue NAD + levels 525 , 526 . Food supplement cocoa flavanol is shown to boost the NAD + and NADH content, stimulate sirtuin metabolism, reduce cellular H 2 O 2 production as well as OxS, and improve mitochondrial function in PASC patients 527 . Increasing NAD + levels could also stabilize telomeres and help recovery of elderly PASC patients 528 .…”
Section: Long-covid/pasc: Precision Nutrition To Reset Virus-induced ...mentioning
confidence: 99%
“…A recent study has reported that epicatechin reduced the cardiac fibrosis in an aged female rat model of pre-heart failure, which correlates with significant reductions in oxidative stress and cytokine levels in the absence of changes in contractile function [130]. Another study by Daussin et al [131] also showed that the administration of cocoa flavanols to mice for 15 days stimulated the NAD metabolism which enhanced the SIRT metabolism and improved the mitochondrial function [131]. In addition, supplementation with a cocoa-carob blend diet rich in flavanols to Zucker diabetic fatty rats counteracted the oxidative stress in diabetic hearts by downregulating the NADPH oxidases, reducing the ROS generation, and modulating the SIRT1/Nrf2 signaling pathway, overall improving the antioxidant defense.…”
Section: Recent Advances In Cocoa Flavanols On Nrf2 Pathway/antioxida...mentioning
confidence: 96%
“…One of the primary targets of SIRT3 deacetylase is metabolism-associated proteins. Studies using SIRT3 knockout mice suggest that SIRT3 has a prominent role in maintaining metabolism homeostasis [ 47 , 85 , 86 , 87 ]. In fact, SIRT3 is heavily involved in various physiological metabolic processes through deacetylation, and thus involved in the process of several diseases of aging, including cancer, heart diseases, metabolic diseases, etc.…”
Section: The Effects Of Sirt3 On Agingmentioning
confidence: 99%